A systematic review on vitamin B for treating peripheral neuropathy - Ang, Cynthia D.
Background: Peripheral neuropathy is a common neurologic disorder of diverse etiologies causing pain, numbness, weakness and other symptoms affecting the individual's activities of daily living and quality of life. Pharmacologic interventions for the treatment of peripheral neuropathy remain non-standardized. The availability and relative affordability of vitamin B make this a frquent treatment option. Studies on its effectiveness, however, show conflicting results. Objectives: The objectives of the study are to determine: (1) the effectiveness of vitamin B in the treatment of adult patients with generalized peripheral neuropathy compared to negative control or placebo, compared to different doses, and compared to active treatment in relieving pain intensity, neuropathic impairments, and neuropathic symptoms; and in improving quality of life and improving nerve conduction study parameters, and (2) the differences in the proportion of participants with adverse events among treatment groups. Study Design: Systematic review of randomized controlled trials and quasi-randomized trails. Search Strategy: We searched the Cochrane Neuromuscular Disease Group Register for randomized trails in August 2005 using specified search terms. We also searched the MEDLINE (January 1966 to September 2005), EMBASE (January 1980 to September 2005), and local databases in September 2005. One author reviewed the bibliography of the identified studies and contacted authors, experts, pharmaceutical companies, medical centers and training institutions to identify additional published or unpublished papers. Selection Criteria: Included studies were randomized controlled and quasi-controlled trials in which vitamin B was compared with a negative control or active treatment. The selection criteria were: (1) studies on adult patients with generalized peripheral neuropathy diagnosed on the basis of symptoms and neurological impairments or symptoms and abnormal neurophysiological test results; (2) studies on vitamin B containing thiamine, riboflavin, nicotinic acid, pyridoxine, or cobalamin (or their derivatives), singly or in combination, given in any dose, by any route, for at least two weeks; folic acid was included only if it was part of a combined preparation containing other vitamin B compounds; (3) studies determining short-term (three months or less) change and long-term (after more than three months) change in pain intensity, neuropathic impairments, neuropathic symptoms, quality of life outcomes, and nerve conduction study parameters, and proportion of participants with adverse events from vitamin B treatment. DATA COLLECTION AND ANALYSIS: Two reviewers independently selected relevant trials, appraised the methodological quality, and extracted the data of eligible studies. We settled disagreements by discussion. For continuous outcomes, we calculated the mean difference (MD) with its 95% confidence intervals (CI). For dichotomous outcomes, we calculated the relative risk (RR) with its 95% CI. For change scores or values, we calculated the difference in the means using the endpoint means. We calculated the I squared statistic to assess heterogeneity across studies. We performed subgroup analyses on studies where vitamin B was compared with placebo or active treatment. We also performed subgroup analysis according to the type of vitamin B. RESULTS: Thirteen studies involving 741 participants were included. There was only one study with adequate randomization. Only four studies had adequate allocation concealment. Vitamin B versus placebo. Vitamin B was more effective than placebo in short-term improvement of vibration perception with 120 to 320 mg/day of benfotiamine administered for eight weeks (MD 0.64, 95% CI 0.34 to 0.93). There was no evidence to suggest that vitamin B was more effective than placebo in short-term reduction of the following outcomes: (1) pain intensity (pooled RR. 0.73, 95% CI 0.44 to 1.23); (2) aggregate neuropathic impairments (RR 0.44, 95% CI 0.19 to 1.03); and (3) numbness (RR 0.63, 95% CI 0.28 to 1.46). There was also no evidence to suggest short-term benefit from vitamin B compare to placebo in improving vibration sensation (RR 0.88, 95%, CI 0.62 to 1.26). There was no evidence to suggest that vitamin B was superior to placebo in long-term reduction of aggregate neuropathic impairments (MD 7.80, 95% CI ?20.32 to 35.92) and neuropathic symptoms (RR 2.00, (95% CI 0.22 to 18.33). There was no evidence to suggest that vitamin B was more effective than placebo in short-term improvement of motor nerve conduction velocity (NCV) of the: (!) median nerve (MD ?0.90, 95% CI ?4.03 to 2.28) and (2) peroneal nerve (MD 0.93, 95% CI-3.76 to 5.62). There was also no evidence to suggest long-term benefit from vitamin B compared with placebo in improving the following outcomes: (1) ?sensory score? (MD ?0.40, 95% CI ?2.82 to 2.02); (2) ?motor score? (MD ?0.81, 95% CI ?3.02 to 1.40); and (3) motor NCV of the peroneal nerve (MD 1.70, 95% CI ?3.60 to 7.00). Vitamin in different doses. Higher doses of vitamin B complex (25 to 50 mg/day thiamine with 50 to 100 mg/day pyridoxine) administered for four weeks was more effective than lower dose (1 to 2 mg/day thiamine with 1 to 2 mg/day pyridoxine) in short-term reduction of: (1) pain (RR 0.13, 95% CI 0.02 to 0.80), (2) aggregate neuropathic impairments ( RR 0.58, 95% CI 0.46 to 0.72), (3) paresthesia (RR 0.17, 95% CI 0.06 to 0.45), and (4) aggregate neuropathic symptoms (RR 0.46, 95% CI 0.35 to 0.59). Vitamin B versus other substance. Two to eight weeks of treatment with vitamin B was less effective than other substance (berlition, cilostazol, cytidine triphosphate or thioctic acid) in short-term improvement of reflex (MD 0.30, 95% CI 0.13 to 0.47) and in short-term reduction of aggregate neuro pathic impairments (pooled RR 7.52, 95% CI 1.12 to 50.63 and standardized mean difference 2.08, 95% CI 1.19 to 2.97) and aggregate neuropathic symptoms (MD 1.40, 95% CI 1.23 to 1.57). There was no evidence to suggest that vitamin B was more effective than epalrestat in long-term reduction of aggregate neuropathic impairments (MD ?0.79, 95% CI ?2.83 to 1.25) and aggregate neuropathic symptoms (MD ?0.11, 95% CI ?4.23 to 4.01). Vitamin B given for four to eight weeks was less effective than other substance (berlition or cilostazol) in short-term improvement of: (1) sensory NCV of the median nerve (weighted mean difference ?4.55, 95% CI ?8.58 to ?0.52) and peroneal nerve (MD ?6.10, 95% CI ?7.65 to ?4.55); and (2) motor NCV of the median nerve (MD ?3.40, 95% CI ?5.09 to ?1.71). There was no evidence to suggest short-term benefit from vitamin B compared to other substance (alpha-lipoic acid or cilostazol) in improving motor NCV of the peroneal nerve (WMD ?0.97, 95% CI ?6.85 to 4.90). There was no evidence to suggest long-term benefit from vitamin B compared to other substance (alpha-lipoic acid or epalrestat) in improving the following outcomes: (1) sensory NCV of the median nerve (MD ?0.35, 95% CI- 4.48 to 3.78); (2) sensory NCV of the ?fibular? nerve (MD ?1.95, 95% CI ?6.22 to 2.32); and (3) motor NCV of the peroneal nerve (MD ?0.20, 95% CI ?1.44 to 1.04). CONCLUSION: There is no evidence to suggest that vitamin B is superior to placebo in short-term improvement of vibration perception based on one study. Evidence also suggests that higher dose of vitamin B complex is more effective than the lower dose in short-term reduction of pain, aggregate neuropathic impairments, paresthesia, and aggregate neuropathic symptoms based on one study. There is emerging evidence to suggest that other substances (berlition, cilostazol, cytidine triphosphate or thioctic acid) may be as effective as more effective than vitamin B in short-term improvement of clinical and neurophysiological outcomes. There is no evidence to suggest long-term benefits on clinical and neurophysiological outcomes from vitamin B compared to placebo or other substances (alpha-lipoic acid or epalrestat). Vitamin B is generally well tolerated with few reported non-serious adverse events.
Thesis--(MS in Clinical Epidemiology) University of the Philippine Manila
Keywords: Peripheral Nervous System Diseases; Vitamin B complex